TRİGONOSEFALİDE "SERBEST ALIN" UYGULAMASI: KALİTATİF VE KANTİTATİF DEĞERLENDİRME - ERDİNÇLER, Pamir and TÜZGEN, Saffet and OĞUZ, Erdal and ÇIPLAK, Nejat and KUDAY, Cengiz (Cerrahpaşa Medical Journal, 2019)
Background and Design. The effectiveness of the "floating forehead" operation for treating trigonocephaly in infants has been assessed. Four children who had undergone this procedure at the Neurosurgery Department of Cerrahpaşa Medical Faculty were reviewed by a quantitative analysis of the anterior cranial fossa development obtained from computerized tomography measurements. Results. Satisfactory cosmetic results were obtained in all patients. Comparison of pre and postoperative anterior cranial fossa measurements showed: 1) correction of acute nasopterional angle; 2) an increase in bipterional distance and a decrease in nasoclinoid distance; 3) moderate correction of acute clinopterional angie. Conclusion. We concluded that the "floating forehead" operation was effective in the treatment of trigonocephaly in infants.